Défis industriels et mouvements sociaux en Haute-Garonne (1967-1978) - Clair Juilliet; Michaël Llopart (Les Cahiers de Framespa)
The objective of our research work of Master 2 was to conduct a thorough review of the economic and social development of the Haute-Garonne Department between 1967 and 1978, as well as the impact of "May-June 1968" in the short and medium term players in the industrial life of Haute-Garonne, first and foremost of which were workers and businesses. It was first necessary to study the major socio-economic issues that arose due to the state of the economy and the continuities and ruptures that marked departmental life, the major theme being the influence of workers' demands. It was equally necessary to assess the extent to which local expectations as regards social matters, industrialization or equipment may have affected the political and economic decisions of the "68 years". It is important to keep in mind that the rest of Haute-Garonne, at the time, a department with little industrial development, and that since the beginning of the twentieth century, all the creations of big industries (Blizzard, SNCASE, Cartridge factory or Tobacco Factory) were part of state initiatives. We have chosen to combine an approach by sectors (Aeronautics, Electronics and Computer Science, Textile, Building and Construction, Paper Carton, Chemistry), by theme (Women and wage practices, the extreme Left, the First of May, immigrant workers, Unions, Support for LIP) and chronological approach (1967-1970, 1971-1974, 1974-1978) to identify patterns and trends within the Department. Two key moments structure our analysis, this concenrs the workers and May-June 1968 and the arrival of the economic crisis after the first oil crisis in 1973-74. In this paper, we intend to present very briefly the results of our two years of research by focusing first on the economic side and then to the social aspect.